2008
DOI: 10.1177/0042098007085103
|View full text |Cite
|
Sign up to set email alerts
|

Residential Segregation and Unemployment: The Case of Brussels

Abstract: disparities opposing city centres and peripheries. In the US for instance, inner cities are usually poor and the catalyst of many social problems, whereas suburbs are more well-off. Brussels exhibits a similar spatial structure since its inner city concentrates unemployed workers and disadvantaged communities, including many unskilled workers and ethnic minorities (see for example, Vandermotten et al., 1999;Thomas and Zenou, 1999; GoffetteNagot et al., 2000;Kesteloot et al., 2001). Residential Segregation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 43 publications
0
44
1
14
Order By: Relevance
“…Reinforcing the social mix in these poor neighbourhoods is seen as a means of reducing these 'neighbourhood effects'. In the case of Brussels, it has been shown that the geographical concentration of social difficulties reinforced these difficulties, in particular as regards access to employment [Dujardin et al, 2008]. In other words, all other things being equal, a person from one of the poorest neighbourhoods has more difficulty in finding a job than a person from a rich neighbourhood.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcing the social mix in these poor neighbourhoods is seen as a means of reducing these 'neighbourhood effects'. In the case of Brussels, it has been shown that the geographical concentration of social difficulties reinforced these difficulties, in particular as regards access to employment [Dujardin et al, 2008]. In other words, all other things being equal, a person from one of the poorest neighbourhoods has more difficulty in finding a job than a person from a rich neighbourhood.…”
Section: Introductionmentioning
confidence: 99%
“…That said, some authors who have examined the spatial mismatch hypothesis have broadened the scope to include such matters (see, for example, Dujardin et al, 2008;Gobillon et al, 2007;Martin, 1997;Weinberg, 2000). Indeed, residential segregation formed the original starting point for James Kain (1968), the pioneer of spatial mismatch studies back in the 1960s.…”
Section: How Do Housing Markets Impact On Poverty and Connectivity?mentioning
confidence: 99%
“…However, in Brussels, two researches question the connection between neighbourhood and mobility. Dujardin, Selod and Thomas (2008) showed that unemployment is exacerbated by residential segregation and that living in a deprived neighbourhood increases the unemployment probability of young adults. However, these deprived neighbourhoods of Brussels are not disconnected from jobs which are concentrated in these areas.…”
mentioning
confidence: 99%
“…Although there is some interdependence with the nearest cities in the south, Brussels is separated from the rest of the WalloniaBrussels Federation by a strip of (Dutch-speaking) land of at least 3.5 km, creating a geographical discontinuity. Actually, Brussels is institutionally defined as a bilingual region enclosed in a Dutch-speaking region, though an extended urban area includes the nearest municipalities from both Flanders and Wallonia (two other regions in Belgium, principally monolingual) (Dujardin, Selod & Thomas, 2008).…”
mentioning
confidence: 99%